2015
DOI: 10.3341/jkos.2015.56.4.477
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Stability after Toric Implantable Collamer Lens Implantation

Abstract: Purpose:To evaluate rotational stability of Toric Implantable Collamer Lens (ICL) implantation to correct myopic astigmatism. Methods: We estimated the degree of Toric ICL rotation together with change in visual acuity and astigmatism in 118 eyes of 66 patients who underwent Toric ICL implantation and had a long-term mean follow-up period of 37 months. Results: After Toric ICL implantation, 107 (91%) out of 118 eyes showed uncorrected visual acuity of 0.8 or better. The mean postoperative astigmatism decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Lee et al found an incidence of 1.7% of rotation in excess of 10° with 98.3% showing excellent rotational stability without decrease in visual acuity. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Lee et al found an incidence of 1.7% of rotation in excess of 10° with 98.3% showing excellent rotational stability without decrease in visual acuity. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, the TICL is widely used for the correction of myopic astigmatism. It has been reported as a predictable, safe, and effective treatment in correcting astigmatism [ 2 , 4 , 7 ]. In this study, we analyzed the visual acuity, refractive outcomes, and rotational stability after implantation of the V4c TICL in 112 eyes of 66 patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to be more accurate and have a lower standard deviation than slit-lamp digital imaging or slit-lamp assessments [ 7 , 14 ]. In the current study, the mean rotation at 12 months was 2.75 ± 2.04°, which is similar to the results in previous studies by Damho et al (2.4 ± 3.8°) [ 7 ] and Ayman et al (2.68 ± 2.11°) [ 14 ]. The maximum TICL rotation in eyes with rotation occurred at 6 months, but there was no statistically significant difference in rotation among the time points.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, rotations occur within the first week [11]. Significant rotations (> 10°) are a rare phenomenon and account for about 1.7 % of all cases [8,9]. A rotation of 15°is sufficient to induce a 50 % decrease of astigmatism reduction.…”
Section: Introductionmentioning
confidence: 99%